Chinese approaches to literature from Confucius to Liang Ch'i-Ch'ao - Rickett, Adele; Rickett, Adele; Yeh, Chia-ying (Princeton legacy library., 1978)
These essays, by Chinese and Western scholars, treat selected aspects of Chinese literary theory, history, and criticism from the age of Confucius to the beginning of the twentieth-century. The topics examined include Confucius as a literary critic (Donald Holzman); the view of ch'i, or vital force, as a decisive element in creative writing (David Pollard); the literary theories of the eleventh-century poet and essayist Ou-yang Hsiu (Yu-shih Chen) and his contemporary Huang T'ing-chien (Adele Rickett); and the seventeenth-century philosopher-poet Wang Fu-chih (Siu-kit Wong). Other essays consider the Ch'ang-chou School of the Ch'ing dynasty (Florence Chia-ying Yeh Chao); the distinctive methods of criticism applied to the Dream of the Red Chamber by the Chih-yen chai commentators (John Wang); and the educative function of fiction as outlined by Liang Ch'i-ch'ao and Yen Fu at the turn of the century (C.T. Hsia).Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.